2020
DOI: 10.1016/j.nicl.2020.102409
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal functional connectivity changes related to dopaminergic decline in Parkinson’s disease

Abstract: Highlights DAT-specific radioligands and PET is one measure of nigrostriatal dopaminergic integrity. Basal ganglia functional connectivity can differentiate patients with PD from healthy controls. Striatal functional connectivity is dependent on the integrity of dopaminergic system. Basal ganglia functional connectivity is compromised by the dopaminergic pathology of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 50 publications
6
49
0
Order By: Relevance
“…Thus, in a final step FC values between clusters of dopaminergic deficiency and cortical clusters were subjected to exploratory correlation analyses. In line with previous results, a close relationship between striatal dopaminergic integrity and functional coupling was traceable 41 . Yet, unlike results from Li et al 41 , our approach poses important advantages, insofar as that we could select study-specific dopamine-depleted structures as seeds instead of general presynaptic function.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, in a final step FC values between clusters of dopaminergic deficiency and cortical clusters were subjected to exploratory correlation analyses. In line with previous results, a close relationship between striatal dopaminergic integrity and functional coupling was traceable 41 . Yet, unlike results from Li et al 41 , our approach poses important advantages, insofar as that we could select study-specific dopamine-depleted structures as seeds instead of general presynaptic function.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous results, a close relationship between striatal dopaminergic integrity and functional coupling was traceable 41 . Yet, unlike results from Li et al 41 , our approach poses important advantages, insofar as that we could select study-specific dopamine-depleted structures as seeds instead of general presynaptic function. Furthermore, we demonstrated a correlation between striatocortical FC and reduced cortical FDG uptake 10 indicating cortical metabolic consequences of reduced coupling to subcortical areas such as the right caudate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, we found that negative modulation of a connection from SN to putamen was significantly larger during RND compared to SEQ in pwPD, and when compared to RND in controls. Similarly, a recent resting-state functional connectivity study showed that pwPD with greater dopaminergic deficits had decreased connectivity between midbrain and putamen ( Li et al, 2020 ). Thus, we speculate that during implicit learning of a motor sequence, the increased drive to recruit the dysfunctional endogenous nigro-striatal dopaminergic system is reflected by similar modulation of SN to putamen connectivity as in controls.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies of the relationship between nigrostriatal dopaminergic innervation and FC have focused on striatal FC. In particular, the correlation of the nigrostriatal innervation, sampled by the striatal TRODAT-1 binding potential 14 , 11 C-Altropane PET 13 , 11 C-PE2I 20 , or with 18 F-FP-CIT PET 12 , with the FC of the striatum has been previously studied in patients with nigrostriatal dopamine loss. Results showed in de-novo, drug-naive PD patients a direct correlation between the posterior putamen dopaminergic innervation and its FC with the dorsolateral frontal cortex contralateral to the MAS, and with the dorsal cerebellum bilaterally 12 .…”
Section: Discussionmentioning
confidence: 99%